Study Some Immunological Parameters in Rabbits Immunized with Cryptococcus neoformans - A. Al-Samarraae, Ikram A.; A. Al-Haddad, Zainab A.; AL-Salmany, Alaa K. M. (Iraqi Journal of Science, 2023)
The aims of this study were to prepare Cryptococcus neoformans killed whole cell antigen and evaluate their effects by using DTH- skin test and the differential white blood cells in local rabbits.Fourteen animals of both sexes were divided randomly into two groups. The first group (7 animals) was immunized with 1 ml of Cryptococcus neoformans killed whole cell antigen (1x 10 cells/ml), subcutaneously. A booster dose was given after 14 days of the first dose. The second group (7 animals) was considered as control group. Based on results of DTH-skin test, no significant differences (P< 0.05) were recorded between the concentrations, 15 mg/ml and 7.5 mg/ml after 24, 48 and 72 hrs., but there was a significant differences (P<0.05) between these concentrations and 7.5 mg/ml and 3.75 mg/ml and control site. There was no significant difference between all types of cells (neutrophils, lymphocytes, monocytes, and eosinophils) of immunized and control groups.